Heterotrophic cultivation of Thraustochytrids using glycerol and saline medium from a dairy effluent - Fortes, Luís André Roque (2017)
Dissertação de mestrado, Engenharia Biológica, Faculdade de Ciências e Tecnologia, Universidade do Algarve, 2016